2023
DOI: 10.1590/acb381523
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and immunohistochemical examination of the effects of ephedrine in rat ovary tissue

Abstract: Purpose: It was aimed to investigate the biochemical and immunohistochemical effects of ephedrine (EPH) in bilateral ovariectomized rats. Methods: Twenty-four Sprague Dawley female rats were divided into three groups: control group: The abdomen was opened and closed without any treatment; ischemia-reperfusion (IR) group: 2 h of ischemia followed by 2 h of reperfusion were allowed to cause IR injury; IR+EPH group: oral EPH solution (5 mg/kg) was administered for 28 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Celik et al found that MDA level was increased in both serum plasma and ovarian tissues in an experimental ovarian IR injury 10 . Toprak et al found that MDA was increased and GSH was decreased in ovarian IR animal model 11 . In our study, both MDA and MPO values were increased in IR group compared to control group, and the increase was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Celik et al found that MDA level was increased in both serum plasma and ovarian tissues in an experimental ovarian IR injury 10 . Toprak et al found that MDA was increased and GSH was decreased in ovarian IR animal model 11 . In our study, both MDA and MPO values were increased in IR group compared to control group, and the increase was statistically significant.…”
Section: Discussionmentioning
confidence: 99%